The Factors Influencing Job Performance Among The Excellent Service Award's Recipient - Wan Noriah, Wan Mohd Shuhaimi (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This study was conducted to identify the influencing factors on job performance among the Excellent Service Award's recipients. The study was based on qualitative research which was through interview with selected informants who are the supporting staff in the studied organization. Most of the informant concluded that they perform well when they are highly motivated by the management. Recognition and rewards and incentives program also motivates employees to increase their productivity and performance on the job as well as the other factors such as relationship with peers and family support. Therefore, this research will helps in understanding the influencing factors on job performance among those who have excelled in their work which have awarded an Excellent Service Award as well as the strategies they have practiced in maintaining their good performance and work challenges they have faced